2023
DOI: 10.1371/journal.pone.0285048
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for intraoperative detection of necrotizing fasciitis in severe soft tissue infections

Abstract: Background Necrotizing fasciitis (NF) is a rare but lethal soft-tissue infection. There is still a paucity of information regarding the diagnostic tools and therapeutic strategies for the treatment of this devastating disease. This study aims to identify important perioperative parameters related to necrotizing fasciitis and to assess their relevance in terms of identifying NF. Methods and material We retrospectively analyzed patients who underwent surgical exploration for suspected necrotizing fasciitis at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Our study showed an overall mortality rate of 18%, which is in line with the existing literature (12%; 22% and 32%) that also examined prognostic factors for NF and found an overall mortality rate [ 15 , 16 , 18 ]. However, the dispersion is striking and should be analyzed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study showed an overall mortality rate of 18%, which is in line with the existing literature (12%; 22% and 32%) that also examined prognostic factors for NF and found an overall mortality rate [ 15 , 16 , 18 ]. However, the dispersion is striking and should be analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…These have already been examined with regard to their reliability for diagnosis and also for prognostic accuracy [ 9 , 10 , 11 , 12 , 13 , 14 ]. Despite the importance of these decision-supporting tools in the acute situation, the prognostic factors for the further course of NF have not yet been conclusively clarified and are still the subject of current research [ 15 , 16 , 17 ]. The present study aims to determine prognostic factors in a large number of patients that are important for the clinical course of necrotizing fasciitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical patient of type II NF is quite young and fit, with a previous history of skin injury, commonly from extremity trauma 5 . Appropriate treatment for NF is the surgical exploration and debridement of the affected tissue remaining the mainstay of therapy, which sometimes requires limb amputation 6 . The most recent Infectious Disease Society of America guideline recommends penicillin plus clindamycin to treat documented group A Streptococcus infections 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The surgical debridement was not performed but treatment with amoxicillin‐clavulanic acid was administered as empiric measure at the time of admission of emergency department. However, this initiated treatment failed to comply with the recommendations 6 . As the causative bacterium of NF was group A Streptococcus, the treatment on arrival of the patient was promptly reconsidered with a combination of amoxicillin‐clavulanic acid and clindamycin.…”
Section: Discussionmentioning
confidence: 99%